Perencanaan Pengembangan Media Pembelajaran Interaktif untuk Meningkatkan Pemahaman Materi Pendidikan Agama Islam (PAI) - Mega Fitri; Riskan Junaidi; Aida Rahmi Nasution; Epa Kristanti (Journal on Education, 2025)
Planning the development of interactive learning media to improve understanding of Islamic Religious Education (PAI) material is an important step in efforts to improve the quality of education in the digital era. Interactive learning media can create a more interesting and effective learning experience, by allowing students to interact directly with teaching materials through various multimedia elements such as text, images, audio, video, and animation. Interactive media-based learning provides an opportunity for students to understand Islamic religious concepts more deeply and applicatively, according to their characteristics and needs. In developing this learning media, careful planning is needed, starting from determining learning objectives, selecting appropriate materials, to designing an easy-to-use interface. In addition, technologies such as Learning Management Systems (LMS), mobile applications, and e-learning can be utilized to improve the accessibility and effectiveness of the teaching and learning process. With the implementation of good interactive learning media, it is hoped that students' understanding of PAI material will increase, and can shape their character and spirituality in everyday life.